Location and volume of intracerebral hemorrhage and their association with outcome - Venkateswara Rao Tangella; Nayyar Iqbal; Gopinath L Nayakar (Journal of Current Research in Scientific Medicine, 2020)
Background: Intracerebral hemorrhage (ICH) accounts for around 10% to 20% of all stroke cases worldwide. It is one of the most fatal and disabling subtype of strokes. Volume of hemorrhage is well documented risk factor for mortality. Aims and Objectives: The objectives of this study is to find whether the location of ICH is an independent risk factor for morbidity and mortality. Material and Methods: It is a prospective cohort study involving adult patients with age more than 18 years presenting with ICH. All patients satisfying inclusion criteria were subjected to CT scan brain. The location of hemorrhages and volume were noted. The four independent variables – gender, presence of hypertension, location and volume of bleed were documented. Their association with modified Rankin scale was calculated using chi – square test, the significance was calculated with P < 0.05. Result: Eighty patients were recruited in the study. 72.5% were male and 27.5% were female. Mean age was 56.25 + 14.3 years. Hypertension was one of the commonest risk factor for ICH (80%). Volume of bleed more than 60 cc was associated with 100% mortality. The majority of the patients presented with ganglio – capsular hemorrhage (64%). Cerebellar and lobar hemorrhage had mortality of 66.7% and 100% respectively. The volume of bleed had odds ratio of 1.2 (P < 0.05). The logistic regression analysis adjusting location of bleed for volume was not significant (P = 0.47). Conclusion: Hypertension is one of the commonest risk factor for ICH. The volume of bleed is an independent predictor of mortality irrespective of location of hemorrhage, gender and other co-morbidity.